IMPLEMENTASI PENDIDIKAN JARAK JAUH (PJJ) PADA MASA PANDEMI COVID-19 (STUDI KASUS: SMA NEGERI 2 PEKANBARU) - Yanti, Rama; Yuliani, Febri (Saraq Opat: Jurnal Administrasi Publik, 2023)
Implementation refers to the implementation of activities that are formulated based on the public policy formulation process. Implementation is the most important stage in public policy, because the success or failure of a policy formulation can be seen from the implementation process. The purpose of this study is to find out how the process of implementing distance education (PJJ) at SMA Negeri 2 Pekanbaru during the covid 19 pandemic. Changes in learning methods in education due to the corona virus outbreak in Indonesia which requires the learning process to be carried out through online media and also face to face limited advance. This research is descriptive in nature with a case study approach and the data required are primary and secondary data derived from observations, interviews, documentation analyzed by researchers so as to obtain accurate and clear data related to the implementation of distance education during the covid 19 pandemic. Implementation of distance education away using several online media, whatsapp, classroom, and zoom. This study uses the implementation model according to George Edward III, namely communication, resources, disposition and bureaucratic structure. The results of the study show that distance education has not been implemented properly because there are still some obstacles encountered when implementing distance education policies, such as limited access to the internet network in several areas in the city of Pekanbaru, with this distance learning method also burdening students' parents in buying internet quota. Students also feel burdened and bored with this distance learning method. Because students also find it difficult to understand the material provided by the teacher because there are still some teachers who only provide material and assignments without prior explanation. Suggestions The school principal should conduct training related to the use of applications used in distance learning methods and teachers must be creative in delivering learning material so that students do not feel bored or burdened with the assignments given.